Mitochondrial remodeling in skeletal muscle underlies exercise-induced reversal of age-associated functional decline in mice and humans - Esther García-Domínguez; Cristina García-Domínguez; José Luis Cabrera-Alarcón; María del Mar Muñoz-Hernández; Pablo Hernansanz-Agustín; Andrea Curtabbi; Julio Domenech-Fernandez; Enrique Calvo; Jesus Vazquez; Antonio L. Serrano; Pura Muñoz-Cánoves; Gloria Olaso-González; et al. (Proceedings of the National Academy of Sciences, 2026)
Loss of skeletal muscle mass and strength are common manifestations of frailty in older people and are linked to reduced quality of life. However, whether mitochondria are mechanistically linked to frailty and how physical activity, or lack thereof, is involved in age-related functional decline are still unknown. We report that exercise-induced improvements in functional capacity, including reduced frailty in old mice, are dependent on mitochondrial adaptations in skeletal muscle at structural, enzymatic, and functional levels. Our preclinical study included a healthy aging mouse line, a transgenic model of robustness, and a muscle-specific mitochondrial-deficient mutant mice, allowing us to assess both mitochondrial plasticity with aging and the necessity of intact mitochondrial function for exercise-induced adaptations. These findings were corroborated by a cross-sectional human study examining the relationship between skeletal muscle mitochondrial function, age, and physical capacity. We analyzed biopsies from 30 donors (men and women, aged 17 to 99 y) stratified into young and older adults with varying functional statuses. Our results indicate that mitochondrial dysfunction in skeletal muscle is associated with the decline in locomotor muscle function in the elderly, highlighting the potential role of exercise or habitual physical activity in mitigating this phenotype. Notably, we demonstrate that skeletal muscle mitochondria maintain plasticity during aging in mice and humans, and that this preserved adaptability can be leveraged to improve muscle performance and overall functional capacity.